2014
DOI: 10.1186/1471-2407-14-189
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale changes in chromatin organization represent the initial steps of tumorigenesis: a transmission electron microscopy study

Abstract: BackgroundNuclear alterations are a well-known manifestation of cancer. However, little is known about the early, microscopically-undetectable stages of malignant transformation. Based on the phenomenon of field cancerization, the tissue in the field of a tumor can be used to identify and study the initiating events of carcinogenesis. Morphological changes in nuclear organization have been implicated in the field of colorectal cancer (CRC), and we hypothesize that characterization of chromatin alterations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 49 publications
5
78
1
Order By: Relevance
“…This relation is derived from the properties of fractal media with conserved mass and volume-as compaction increases locally, the variations in mass density (heterogeneity) must also increase. Previous molecular dynamics simulations have further confirmed that increases in δn*L c correspond to an increase in macromolecular compaction, and experimental results have shown that this increase within the nucleus quantitatively describes an increase in chromatin heterogeneity (21,25,26).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…This relation is derived from the properties of fractal media with conserved mass and volume-as compaction increases locally, the variations in mass density (heterogeneity) must also increase. Previous molecular dynamics simulations have further confirmed that increases in δn*L c correspond to an increase in macromolecular compaction, and experimental results have shown that this increase within the nucleus quantitatively describes an increase in chromatin heterogeneity (21,25,26).…”
Section: Resultsmentioning
confidence: 68%
“…One of the primary features of tumorigenesis is a shift in the fractal physical organization of chromatin, correlating both with the formation of tumors and their invasiveness. In early carcinogenesis, we have previously applied a fixed-cell-imaging technique, partial-wave spectroscopic (PWS) microscopy and transmission electron microscopy (TEM), to detect physical changes in the chromatin nanoarchitecture, indicating that the topology of chromatin is a critical component in cellular function at the earliest stages of tumor formation (21). PWS microscopy allows examination of the intracellular organization concealed by the diffraction limit with length scale sensitivity in the range of 20-200 nm, the range at which existing label-free live-cell imaging techniques are deficient, due to the relationship between the nanoscale spatial variations of macromolecular density and the resulting variance in the spectrum of backscattered light (22,23).…”
Section: Significancementioning
confidence: 99%
“…We believe that all of the above factors must have contributed to the observed fourfold difference in the RI correlation lengths within cancer cell lines and histologically normal tissue. Lastly, based on previous studies focused on the quantification of the internal organization of biomaterials via light or electron microscopy, 20,23 we believe that data acquired from 10 to 30 fields of view (30 to 150 biological cells depending on cell type) will be sufficient to account for biological variability and determine σ n Δ and l c values typical for a given biological sample. In the future, automated image acquisition can be implemented to acquire and analyze whole-slide images of biological samples (up to 1500 images per slide as has already been implemented elsewhere).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PWS is a promising tool for detecting early-stage microscopically undetectable tumorigenic alterations in biological cells and tissues such as changes in chromatin organization [9].…”
Section: Full-spectrum Analysismentioning
confidence: 99%
“…PWS microscopy achieves sensitivity to nanoscale structures within biological cells by using the spectroscopic content of microscope images, and quantitatively measures nanoarchitectural changes in cells associated with carcinogenesis [6,7]. These intracellular, macromolecular alterations are recognizable as some of the earliest indicators of carcinogenesis and are detectable throughout an affected organ, not just at the tumor site, via a phenomenon known as the field effect of carcinogenesis [8,9]. Because PWS is sensitive to nanoscale structure below the diffraction limit of traditional microscopy systems, including those used for wholeslide imaging, it can be used for minimally invasive cancer screening via the field effect.…”
Section: Introductionmentioning
confidence: 99%